Computer‐Aided Discovery of Potent Broad‐Spectrum Vaccine Adjuvants. (23rd March 2023) - Ma, Juan; Wang, Shenqing; Zhao, Chuanfang; Yan, Xiliang; Ren, Quanzhong; Dong, Zheng; Qiu, Jiahuang; Liu, Yin; Shan, Qing'e; Xu, Ming; Yan, Bing; Liu, Sijin
Abstract: Adjuvants stimulate the immune system to vigorously respond to a vaccine. While current adjuvants such as aluminum salts and oil‐in‐water emulsions have been used for decades, they do not generate broad and long‐lasting responses in many vaccines. Consequently, more potent adjuvants are needed. Here, using computer‐aided molecule design and machine learning, we discovered 2 new, broad‐spectrum adjuvants that can boost vaccine responses. Our library containing 46 toll‐like receptor (TLR)‐targeting agonist ligands were assembled on Au nanoparticles. Comprehensive in vitro, ex vivo and in vivo studies showed both leads promoted dendritic cell activation via multiple TLRs and enhanced antigen presentation to T cells. When used together with tumor‐specific antigens to immunize mice against B16‐OVA melanoma and 4T1‐PD1 breast cancer, both adjuvants unleashed strong immune responses that suppressed tumor growth and lung metastases. Our results show computer‐aided design and screening can rapidly uncover potent adjuvants for tackling waning immunity in current vaccines. Abstract : New Au nanoparticle (AuNP) adjuvants are prepared through computer‐aided molecule design and machine learning to discover agonist ligands, and sulfur‐Au coordination chemistry guided well‐ordered presentation of ligands on AuNP surface. These AuNP adjuvants show advantages in multi‐toll like receptor (TLR) targeting and application as broad‐spectrum adjuvants to boost robust multifaceted anti‐tumor vaccine responses.